Mastering Microsoft SQL server 2005 - Gunderloy, Mike (Wiley Publishing, 2006)
Microsoft's SQL Server 2005 Express Edition is the perfect fit if you're a small business owner, trainer, or student who doesn't need all the bells and whistles of the full version of SQL Server 2005. In this comprehensive guide written by two SQL Server experts, you'll find step-by-step explanations and simplified management tools for using SQL Server Express in smaller-scale but still mission-critical situations. With a focus on practical tasks, the book thoroughly covers both database administration and development, smoothly moving you from beginner to advanced subjects